A case for updating the WHO Safe Childbirth Checklist to improve newborn care: Experience from seven Asia and Pacific countries. (1st October 2020) - Sobel, Howard L.; Murray, John C. S.; Mannava, Priya; Mathai, Matthews; Silvestre, Maria Asuncion A.
Abstract: The WHO Safe Childbirth Checklist (the SCC) is a clinical tool developed to help health workers follow evidence‐based maternal and perinatal care practices at childbirth. Newborn delivery care practices at facilities in seven countries in East Asia and the Pacific were compared to practices checked by the SCC. The analysis found that the SCC does not incorporate several key evidence‐based practices around birth demonstrated to prevent newborn morbidity or mortality, or harmful practices associated with increased risks. A revision of the standard SCC is needed to maximise its potential to improve newborn outcomes. This can be initiated under the coordinating umbrella of WHO, but must ensure that the realities of labour and childbirth practices in low‐ and middle‐income countries are considered and addressed.